Entropy generation analysis as a design tool—A review. (March 2015) - Sciacovelli, A.; Verda, V.; Sciubba, E.
Abstract: There is an acknowledged growing need for efficient and sustainable systems that use available energy resources in an "optimal" (including constraints) way. Such a goal cannot be effectively achieved without taking into account the limits posed by the second law of thermodynamics. A possible approach consists in the so-called entropy generation analysis, which possesses key features making it more attractive than traditional energy balance approaches. In fact, entropy generation analysis allows for a direct identification of the causes of inefficiency and opens up the possibility for designers to conceive globally more effective systems. Furthermore, thanks to its direct derivation from basic thermodynamic principles, entropy generation analysis can be in principle used for any type of energy conversion system. These attractive features have made entropy generation analysis a popular thermodynamic method for the design and the optimization of less unsustainable systems. This paper presents a critical review of contributions to the theory and application of entropy generation analysis to different types of engineering systems. The focus of the work is only on contributions oriented toward the use of entropy generation analysis as a tool for the design and optimization of engineering systems. A detailed derivation of the existing entropy generation formulations is first presented, and the two more popular approaches are discussed: the entropy generation minimization (EGM) and the entropy generation analysis (EGA). The relevant literature is further classified in two categories, depending on whether the level of the analysis is global or local. This review will further clarify the use of entropy generation-based design methods, indicate the areas for future work, and provide the necessary information for further research in the development of efficient engineering systems.